Exploring Translation Competence through Think-Aloud Data: A Case Study - Kodura, Małgorzata Maria (Acta Neophilologica, 2023)
The aim of this paper is to explore the value of think-aloud methodology in the process of translation competence development. The paper describes concepts of translation competence, with particular focus on the PACTE and EMT models. When considering the acquisition of translation competence as a continuous process, it is important to precisely define its starting point. This can be achieved by recording the translation process through verbalisations of thoughts. The main part of the paper is a case study presenting the application of TAP data in the translation course. The conclusions may be useful for designing translator training curricula and verifying educational results.